Prevalence of urinary incontinence among subjects with low back pain - P.PONMATHI,; T.JAYALAKSHMI,; PROF.V.P.R.SIVAKUMAR, (International Journal of Pharma and Bio Sciences, 2017)
Low back pain is the pain in lower back area that can be related to problems with the lumbar spine, the disc etc. Urinary incontinence is the complaint of involuntary leakage of urine or immediate proceeded by urgency. The core muscle composed of paraspinal muscle in the back, the abdominal muscle in the front, the diaphragm in the upper abdomen and pelvic floor muscle in the lower abdomen. To investigate the prevalence of urinary incontinence in low back pain subjects. 230 subjects with history of diagnosed low back pain were included in the study. Urinary incontinence was assessed by the Questionnaire for Urinary Incontinence Diagnosis (QUID). There was a prevalence of incontinence among male subjects with back pain (31.9%) and among female subjects with back pain (44.5%), so the assessment of incontinence proves important among low back patients.